2019
DOI: 10.1016/j.ajhg.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Mutations in KCNN3 Encoding the Small-Conductance Ca2+-Activated K+ Channel SK3 Cause Zimmermann-Laband Syndrome

Abstract: Zimmermann-Laband syndrome (ZLS) is characterized by coarse facial features with gingival enlargement, intellectual disability (ID), hypertrichosis, and hypoplasia or aplasia of nails and terminal phalanges. De novo missense mutations in KCNH1 and KCNK4, encoding K þ channels, have been identified in subjects with ZLS and ZLS-like phenotype, respectively. We report de novo missense variants in KCNN3 in three individuals with typical clinical features of ZLS. KCNN3 (SK3/KCa2.3) constitutes one of three members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 80 publications
(130 reference statements)
2
48
0
1
Order By: Relevance
“…1 Regarding the consequences of in vivo mutations, a rare S436C mutation in SK3 channels leads to a disease called the Zimmermann-Laband syndrome affecting the development of many types of tissue such as gums, nails and facial features. 19 This mutation located at the interface between calmodulin and one of the channel's subunits induces a faster and more complete activation of the corresponding channel similarly to what is observed in the Nam's paper. Indeed, the replacement of the serine 436 by a cysteine 19 induces an increase of the local hydrophobicity and reduced propensity to create hydrogen bond leading to structural changes also affecting the gating.…”
Section: Deciphering the Molecular Mechanism Of Sk2 Channel Activatiosupporting
confidence: 60%
“…1 Regarding the consequences of in vivo mutations, a rare S436C mutation in SK3 channels leads to a disease called the Zimmermann-Laband syndrome affecting the development of many types of tissue such as gums, nails and facial features. 19 This mutation located at the interface between calmodulin and one of the channel's subunits induces a faster and more complete activation of the corresponding channel similarly to what is observed in the Nam's paper. Indeed, the replacement of the serine 436 by a cysteine 19 induces an increase of the local hydrophobicity and reduced propensity to create hydrogen bond leading to structural changes also affecting the gating.…”
Section: Deciphering the Molecular Mechanism Of Sk2 Channel Activatiosupporting
confidence: 60%
“…Although, increased K + conductance may not be traditionally associated with hyperexcitability and epilepsy, several studies have shown that inhibition of K + conductances improves learning and memory in wild-type mice, or seizure susceptibility in a model of Angelman syndrome ( Stackman et al, 2002 ; Fontán-Lozano et al, 2011 ; Sun et al, 2019 ). Furthermore, gain-of-function mutations in several K + channels including KCNQ2, KCNQ3, KCNQ5, BK, SK3, KCNT1, and K V 4.2 have been reported in genetic epilepsy and developmental disorders ( Niday and Tzingounis, 2018 ; Bauer et al, 2019 ). Because KCNQ2-DEE patients present with seizures in the first days of life, targeting the underlying cause might not be effective if started late in the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…46 Mutation of the equivalent serine in SK3 channels to cysteine (S436C) also increases apparent Ca 2+ sensitivity. 47 This CaM-S 45 A interaction interface was then explored as potential binding pocket of small molecule modulators of the channels. 46 Now that we know that CaM interactions with both the CaMBD (HA and HB helices) and the S4-S5 linker (S 45 A and S 45 B helices) are crucial for the apparent Ca 2+ sensitivity of the channels, then what about the interactions between the CaMBD and the S4-S5 linker?…”
Section: Discussionmentioning
confidence: 99%